Effect of misonidazole and hyperthermia on the radiosensitivity of a C3H mouse mammary carcinoma and its surrounding normal tissue. - Overgaard, J. (Nature Publishing Group, 1980)
Both misonidazole (MISO) and hyperthermia are known to enhance the radiation response of hypoxic cells, and to be selectively cytotoxic against cells in a hypoxic and acidic environment. The ability of these conditions to modify the effect of irradiation and their individual relationship was studied in a C3H mammary carcinoma and its surrounding skin. Simultaneous treatment with MISO, hyperthermia and radiation increased the radiation effect, with enhancement ratios (ER) of up to about 15 (1 mg/g MISO and 43.5 degrees C for 60 min.). However, such treatment also caused a smaller hyperthermic radiosensitization of the normal tissue, so that the therapeutic ratio was only increased by a factor of about 3 compared to radiation alone. Simultaneous MISO and radiation followed by hyperthermia 4 h later gave a moderate enhancement, with ER up to 3 in the tumour, but with no enhancement of the normal tissue, so that there is a similar 3-fold increase in therapeutic gain. The mechanism by which MISO and hyperthermia enhanced the radiation response may be explained as an independent action of the hypoxic radiosensitization of MISO and the selective hyperthermic cytotoxicity against acidic and chronic hypoxic cells; simultaneous hyperthermia added a further heat-induced general radiosensitization. Surprisingly, no MISO cytotoxicity could be detected in this tumour system, with or without simultaneous hyperthermia. The results indicate that in the proper treatment schedule, MISO may be a valuable addition to a combined hyperthermia and radiation treatment. IMAGES: